Peran Pemuda dalam Pelestarian Wayang Suket Sebagai Aktualisasi Nilai Moral Pancasila - Awaliyah, Siti; Shofa, Abd. Mu’id Aris; Habibi, Muhammad Mujtaba (Universitas Negeri Malang, 2019)
This study aims to reveal the role of youth in the preservation of wayang suket in the Gubuk Baca Lentera Negeri (GBLN) and see the actualization of the Pancasila moral values in the traditional Suket puppet play. This study was conducted on a group of young people who are members of the Gubuk Baca Lentera Negeri in Sukolilo Village, Jabung District, Malang Regency. This study uses a qualitative method, the subject of the study is the Gubuk Baca Lentera Negeri and the object of study is the role of youth in the preservation of wayang suket as the actualization of the Pancasila moral values. Data collection methods in this study use interviews, observations, field notes, literature, internet, and documentation. The results of this study have illustrated that the Gubuk Baca Lentera Negeri has preserved wayang suket and in the process of making and story of wayang suket, there is a moral value of Pancasila.